Chinoiscenic redefining Chinese-Filipino event spaces through the design of a celebratory landscape - Cheng, Gail Lauren D. (Quezon City College of Architecture, University of the Philippines Diliman, 2014)
The Chinese-Filipino community have, for a long time now, become a vital part of the Philippine’s society. The have built a culture that exhibited not only the Chinese culture but Filipino values as well. The principles, customs and traditions of this community revolved around the family and the importance that is given to it.
One of the many manifestations of this importance given to the family can be seen in the celebration of special moments, big and small, of the Chinese-Filipino community. Unfortunately though, the celebrations have been given a notion and a abstract limitation that they be celebrated indoors – like restaurants.
The study proposes a redefining of this notion on the Chinese-Filipino events spaces through the designing of a celebratory space with the use of information gathered from intense research, consultations and such.
In conclusion to the study, an effective design has been created that would serve the different types of celebrations that the Chinese-Filipino community practices. This design provides both indoor and outdoor spaces that allow a better experience and commemoration of special moments. At the same time this proposed development would not only provide a venue for a cultural immersion but also jump start for the development of these types of spaces.
Best Thesis (Landscape Architecture) AY 2013-2014, 2nd place
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Event spaces